Perancangan Aplikasi Pembayaran Sumbangan Pembinaan Pendidikan (SPP) Bulanan Santri pada Pondok Pesantren Syekh Hamzah Al-Fansury Kota Subulussalam - Nurhasanah, Putri; Ahmad, Adi; Alfina (Jurnal Manajemen Sistem Informasi (JMASIF), 2025)
Pondok Pesantren Syekh Hamzah Al-Fansury in Subulussalam City emphasizes high-quality educational services, including managing the monthly Sumbangan Pembinaan Pendidikan (SPP) payments for approximately 300 students. The growing number of students requires the development of a more efficient and detailed payment system. Currently, payments are processed manually, which can be inefficient. Transactions are recorded using cards and then manually entered into a ledger by the treasurer. This system risks errors and data loss, especially if a payment card is lost. The introduction of an SPP payment application is expected to improve data efficiency and security. Payments will be accurately recorded and securely stored in a database. The use of a computerized system will also help minimize errors and facilitate access to payment data, particularly in generating financial reports. This study aims to develop a web-based SPP payment application for Pondok Pesantren Syekh Hamzah Al-Fansury. A qualitative approach was used to understand the needs of potential users, while the waterfall method of software development was chosen to ensure a structured design process. The results show that the application effectively simplifies the payment process, generates receipts, and presents reports accurately. This application is expected to provide an effective solution to enhance the quality of SPP payment services for students at Pondok Pesantren Syekh Hamzah Al-Fansury.